High-performance electric motor with reduced rare-earth magnets for electric vehicle application - Murugan, Paramesh (Nanyang Technological University, 2024)
Considering the growing global environmental concerns, there has been significant focus on sustainable energy solutions, specifically in relation to electric vehicles (EVs). Most electric vehicle motors currently utilize rare-earth elements, which are rare. Therefore, the purpose of this report is to examine the utilization of reduced-rare earth materials in attaining high-performance levels of performance for electric vehicle (EV) applications. Permanent magnet (PM) motors, frequently utilized in electric vehicles (EVs), heavily depend on rare earth materials. These materials present environmental and supply chain difficulties due to their restricted availability and geopolitical uncertainties. This report has examined various types of electric motors utilized in electric vehicle (EV) applications, with a primary emphasis on high-performance motors that minimize the use of rare earth materials. The focus of this work is proposing and designing a new V-shaped permanent magnet motor that uses only very small quantities of rare earth material without compromising its performance too much. An experimental analysis was conducted to analyse the performance of V-shaped permanent magnet synchronous motors (PMSMs) using reduced-rare earth materials. The results showed that these motors exhibit high torque density. Thereafter, torque density, efficiency, and power factor have been used for performance comparison in post-simulation by the use of the JMAG software. The suggested design of the PM motor utilizes sophisticated magnetic circuit configurations to enhance the distribution of magnetic flux, reducing the need for rare earth magnets. The project seeks to decrease the amount of rare earth materials used in the motor by investigating different magnet materials and motor configurations. This reduction in rare earth content will not compromise the motor's performance metrics, including power density, torque output, and efficiency.